The Theology of Music in African Spiritualities - Dorcas Juma (African Theological Journal for Church and Society)
This paper examines the theology of music within African spiritualities through a post-Covid-19 perspective, centring on Psalm 121 in dialogue with the song Jerusalema by Master KG featuring Nomcebo. Music, as a theological tool, offers transformative possibilities for encountering God during times of emptiness and despair. In particular, Jerusalema emerged as a global anthem of hope during the Covid-19 pandemic, symbolising resilience and life affirmation. By dancing to its beat across cultures, people worldwide experienced joy amidst suffering. This study proposes that the theology of music has the power to renew spiritualities, creating space for experiencing God in both absence and fullness. It also highlights how African music more broadly, fosters ongoing conversations on sustaining hope through spiritual practices. Through a post-pandemic hermeneutical lens, this paper puts the biblical song of ascent in Psalm 121 in dialogue with Jerusalema to offer a prophetic vision of renewed hope and flourishing in pain and suffering.